Imaging Assessment of Lung Tumor Angiogenesis: Insights and Innovations - Yip, Connie; Cook, Gary J.; Weeks, Amanda; Goh, Vicky J. (Seminars in Respiratory and Critical Care Medicine, 2014)
Lung cancer is the leading cause of cancer death in the United States. It is estimated that more than 228,000 new cases will be diagnosed in 2013, accounting for approximately 159,000 or 27% of all cancer deaths. Survival in these patients remains poor despite advances in surgery, definitive radiotherapy, and chemotherapy for primary and metastatic non-small cell lung cancer. Five-year relative survival rates remain at 27% for regional disease and 54% for node-negative disease. With the increasing personalization of therapy, there remains a need for better prognostic and predictive markers to direct patient management in lung cancer. Hypoxia and angiogenesis play an important role in the development and progression of lung cancer. Targeted and non-targeted imaging techniques in the preclinical and clinical setting, combined with advanced postprocessing techniques to assess tumor heterogeneity, may enable clinicians to better characterize lung tumors, and to predict and assess response to treatment. In this review, we summarize our current understanding of angiogenesis in lung cancer and discuss the available imaging techniques to assess this in the preclinical and clinical setting.
Keywords: lung cancer; angiogenesis; review